2022
DOI: 10.1007/s41130-022-00173-3
|View full text |Cite
|
Sign up to set email alerts
|

Food, climate and biodiversity: a trilemma of mineral nitrogen use in European agriculture

Abstract: Mineral nitrogen (N) application in agriculture has significantly increased food production over the past century. However, the intensive use of N-fertilizers also impacts negatively the environment, notably through greenhouse gas emissions and biodiversity loss and remains a major challenge for policymakers. In this paper, we explore the effects of a public policy aiming at halving agricultural mineral nitrogen use across the European Union (EU). We investigate the impacts on food security, climate mitigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Sutton et al (2011) evaluated the environmental costs associated with the impact of atmospheric and water pollution on ecosystems and human health in EU Member states at €70-320bn euros per year. The magnitude of this sum suggests that the social costs of N fertilizers in Europe now offset a large proportion of the gains and that the social benefits of reducing nitrogen use would exceed the private losses (Prudhomme et al, 2022).…”
Section: Synthetic Nitrogen Use In Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…Sutton et al (2011) evaluated the environmental costs associated with the impact of atmospheric and water pollution on ecosystems and human health in EU Member states at €70-320bn euros per year. The magnitude of this sum suggests that the social costs of N fertilizers in Europe now offset a large proportion of the gains and that the social benefits of reducing nitrogen use would exceed the private losses (Prudhomme et al, 2022).…”
Section: Synthetic Nitrogen Use In Agriculturementioning
confidence: 99%
“…Our primary focus is to analyze the consequences for agricultural production, prices, land use changes, and GHG emissions at both local (EU) and global levels. Other aspects, such as biodiversity and carbon impacts, have been explored in (Devaraju et al, 2022), and a summary of the policy effects can be found in a related publication (Prudhomme et al, 2022).…”
mentioning
confidence: 99%